Predictors and Sequelae of Postoperative Delirium in Geriatric Hip Fracture Patients. (3rd December 2018) - Arshi, Armin; Lai, Wilson C.; Chen, James B.; Bukata, Susan V.; Stavrakis, Alexandra I.; Zeegen, Erik N.
Introduction: Perioperative delirium in elderly hip fracture patients has been correlated with significant morbidity. The purpose of this study was to determine the preoperative risk factors for and short-term sequelae of postoperative delirium in geriatric hip fracture patients. Methods: We queried the American College of Surgeons National Surgical Quality Improvement Program to identify geriatric (≥65 years) patients who sustained operative hip fractures in 2016. Cohorts of patients with and without documented postoperative delirium were identified. Primary data on patient demographics and comorbidities were collected and correlated with postoperative complications and hip fracture outcome measures. Multivariate regression was used to compute risk-adjusted odds ratios (OR) of risk factors and sequelae of delirium. Results: In total, 8, 439 geriatric hip fracture patients were identified of whom 2, 569 patients (30.4%) had postoperative delirium. Age (OR 1.03 [1.02-1.04, p < 0.001), white race (OR 1.54 [1.19-2.00], p = 0.001), American Society of Anesthesiologists classification (OR 1.20 [1.07-1.36], p = 0.003), baseline dementia (OR 2.46 [2.11-2.86], p < 0.001), and preoperative delirium (OR 10.06 [8.12-12.45], p < 0.001) were independent risk factors for postoperative delirium in multivariate analysis. Patients with postoperative delirium had a significantly higher risk-adjusted 30-day mortality (12.0% vs. 4.8%, OR 2.22 [1.74-2.84], p < 0.001) and morbidity profile. Postoperative delirium was also independently associated with higher rates of discharge to (OR 1.65 [1.32-2.06], p < 0.001) and prolonged stay in (OR 1.79 [1.53-2.09], p < 0.001) an inpatient facility, hospital readmission (OR 1.94 [1.58-2.38], p < 0.001) and hospital length of stay (7.6 ± 5.0 vs. 6.1 ± 4.1 days, p < 0.001), as well as lower rates of immediate postoperative weight bearing (OR 0.73 [0.63-0.86], p < 0.001). Discussion: Postoperative delirium is a common occurrence in geriatric hip fractures with multiple risk factors. Delirium portends higher mortality and worse perioperative hospital-based outcomes. Conclusions: Multidisciplinary foreknowledge and management efforts are warranted to mitigate the risk of developing delirium, which strongly predicts perioperative morbidity, mortality, and hip fracture outcomes.